2019
DOI: 10.1200/jco.2019.37.15_suppl.8504
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant nivolumab (N) or nivolumab plus ipilimumab (NI) for resectable non-small cell lung cancer (NSCLC): Clinical and correlative results from the NEOSTAR study.

Abstract: 8504 Background: Neoadjuvant immune checkpoint inhibitors (ICIs) induce major pathologic response (MPR) rates of 20 to 45% in resected NSCLCs. We report the results of NEOSTAR - a phase 2 trial of neoadjuvant N or NI for NSCLCs. Methods: Pts with stage I-IIIA (single N2) resectable NSCLC (AJCC 7th), PS 0-1, were randomized to N (3 mg/kg IV, D1, 15, 29) or N plus I (1 mg/kg IV, D1) followed by surgery (n = 44). Primary endpoint: MPR (≤10% viable tumor), hypothesized to be higher than MPR to induction chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
158
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 0 publications
6
158
1
Order By: Relevance
“…Grade 3 or higher TRAEs were observed in 33% of enrolled patients in our study, a numerically higher rate than that reported in an interim presentation of the NEOSTAR study, an ongoing phase II single-center study which randomized 44 patients with resectable NSCLC to neoadjuvant nivolumab or nivolumab plus ipilimumab. 11 Differences in toxicity rates are likely attributable to sample size and overall the observed rate of ≥G3 TRAEs in our study was similar to that seen with nivolumab plus ipilimumab in advanced NSCLC 6 and in neoadjuvant studies of resectable melanoma. 12 Nevertheless, the toxicity in our study arm exceeded that reported in neoadjuvant studies of anti-PD1 monotherapy 4 11 13 14 and combination ICB plus chemotherapy, 15 16 which was a major determinant in our decision to terminate this study arm early.…”
Section: Discussionsupporting
confidence: 70%
“…Grade 3 or higher TRAEs were observed in 33% of enrolled patients in our study, a numerically higher rate than that reported in an interim presentation of the NEOSTAR study, an ongoing phase II single-center study which randomized 44 patients with resectable NSCLC to neoadjuvant nivolumab or nivolumab plus ipilimumab. 11 Differences in toxicity rates are likely attributable to sample size and overall the observed rate of ≥G3 TRAEs in our study was similar to that seen with nivolumab plus ipilimumab in advanced NSCLC 6 and in neoadjuvant studies of resectable melanoma. 12 Nevertheless, the toxicity in our study arm exceeded that reported in neoadjuvant studies of anti-PD1 monotherapy 4 11 13 14 and combination ICB plus chemotherapy, 15 16 which was a major determinant in our decision to terminate this study arm early.…”
Section: Discussionsupporting
confidence: 70%
“…Compared with the Checkmate-159 study, 17 a similar MPR rate (40.5% versus 45%) and superior ORR (20.0% versus 10%) were observed in our study. Regarding the NEOSTAR study, 26 a superior MPR (40.5% versus 17%), similar ORR (20.0% versus 22%), and pCR (8.1% versus 9%) was identified in current study compared with single nivolumab neoadjuvant treatment group. Moreover, the median degree of pathologic remission in primary tumor was 50% in our study.…”
Section: Discussionsupporting
confidence: 52%
“…Another G5 TRAE was pneumonia-caused death after operation that was also reported in single nivolumab treatment group of the NEOSTAR study. 26 Two patients postponed operation because of treatment-related grade 2 AE. Therefore, generally, neoadjuvant sintilimab was well tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…29 In a recent presentation, the NEOSTAR phase 2 trial demonstrated higher rates of major pathological response in patients receiving combination nivolumab plus ipilimumab compared with those receiving nivolumab monotherapy before surgery. 30 Overall, both therapeutic regimens were well tolerated; however, surgical complications included 2 bronchopleural fistulas and 8 air leaks. 30 These early results are promising from a feasibility and safety standpoint.…”
Section: Current Literature and Ongoing Trialsmentioning
confidence: 91%
“…30 Overall, both therapeutic regimens were well tolerated; however, surgical complications included 2 bronchopleural fistulas and 8 air leaks. 30 These early results are promising from a feasibility and safety standpoint. They suggest limited surgical delays and adequate resection; however, the technical considerations in using these therapies preoperatively has generated little discussion to date.…”
Section: Current Literature and Ongoing Trialsmentioning
confidence: 91%